EVALUATION OF IMPLEMENTATION STUDENT SKILL COMPETENCY ASSESSMENT OFFICE ADMINISTRATION - Aziz FIRMANA (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2022)
This evaluation aimed to determine the context of implementation student skill competency assessment office administration at Dharma Karya Vocational High School, South Jakarta, the readiness of students, educators and education personnel, financing, facilities and infrastructure, the process of implementing the assessment, and knowing the achievement of program implementation. The method used in this evaluation is descriptive qualitative method by taking empirical data and facts, and the model used is the CIPP model (Contex, Input, Process, Product). Data collection was carried out scientifically which included observation, structured interviews, and documentation. Interviews were conducted with the Principal, Deputy Head of Curriculum, Deputy Head of Facilities and Infrastructure, Head of Office Administration Department, Chair of the Examination Committee, Internal Examiners, External Examiners, and students. Then the data obtained were analyzed using the triangulation method of sources, display data, and conclusions. The conclusion of the evaluation research, that the background for the activity of student skill competency assessment at the Dharma Karya Vocational High School, South Jakarta, is the existence of a Government policy towards Vocational High Schools that are in accordance with environmental needs and the vision and mission of the school.